Current Pattern of Parasuicide in Our Society - Yuzana, Mohd Yusop; Lukman@Zawawi, Mohamad; Mohamad Razali, Abdullah (2018)
Parasuicide and suicide have been a notable subject in the realm of public health. Though parasuicide history is considered to strongly predict completed suicide, the patterns of method, location and period of suicide attempt are not well-known, especially in upper middle-income country such Malaysia. Thus far, no complete count is kept on parasuicide by several agencies involved. The aim of this study is to report the current pattern and prevalence of parasuicide in Malaysia. The data were collected from the online media from 1 January 2017 to 31 March 2018 (15 months). In total, 21 incidences met the inclusion criteria. Across all cases, the leading method of parasuicide in our society pick out by the subjects is jumping from high structured building, more specifically residential area such as condominium and flats, at daylight, compared to hours of darkness. There is a cross-national variability in the current pattern of parasuicide manners, with strong uniformity in the method and period preferences for these behaviours. These findings have significant implications for the prevention and prognostication of parasuicidal actions.